Effects of Increasing Dietary Lysine on Performance of Lactating Sows in Commercial Conditions - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; S. S. Dritz; R. D. Goodband; S. J. Kitt; E. W. Stephenson (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 710 mixed parity sows (Line 241; DNA, Columbus, NE) were used in a 21-d study to determine the effect of standardized ileal digestible (SID) lysine (Lys) intake during lactation on sow and litter performance and subsequent reproductive performance of primiparous and multiparous sows housed in a commercial production system. On d 112 of gestation, females were weighed and blocked by BW within expected farrowing date and parity (1 to 7) and randomly assigned to 1 of 4 dietary treatments within blocks. Dietary treatments were corn-soybean meal-based and consisted of increasing SID Lys (0.75, 0.90, 1.05, and 1.20%). Treatments were formulated by increasing both crystalline Lys and soybean meal to maintain a similar soybean meal to crystalline Lys ratio. Other feed-grade amino acids (AA) were added as needed to maintain a similar ratio to Lys across treatments. All other nutrients met or exceeded the NRC4 requirement estimates. Dietary metabolizable energy was the same across all dietary treatments. Sow BW at weaning increased (quadratic, P = 0.046), and sow BW loss from post-farrow to weaning or d 112 to weaning decreased (quadratic, P ≤ 0.01) as SID Lys increased. Sow backfat loss increased (linear, P = 0.028) as SID Lys increased. Conversely, longissimus muscle depth loss decreased (linear, P = 0.002) as SID Lys increased. Percentage of females bred by d 7 after weaning increased (linear, P = 0.047) as SID Lys increased in parity 1 sows, with no difference in parity 2 or 3+ sows. Litter weight at d 17 and litter gain from d 2 to 17 increased (quadratic, P = 0.01) as SID Lys was increased up to 1.05%, with no improvement thereafter. For subsequent litter characteristics, there were no differences in total born, percentage born alive, stillborn, or mummies. In conclusion, our results suggest that increasing dietary SID Lys can reduce sow protein loss in lactation. The optimal level of dietary SID Lys required by the sow may vary based on response criteria and parity.
Keywords: gilt; lactation; lysine; reproduction; sow